منهج محمد علي السايس في كتابه "تفسير آيات الأحكام - عبدالله أحمد الزيوت (İslami İlimler Dergisi)
This research investigates the methodology of  Muhammad Ali al-Sayis in his book "TafsirAyat al-Ahkam". It gives an overview about the author and the book,his method, and sources. The research also shows that the book has positive aswell as negative aspects. For example, the author was interested intransmissions freeness of biasness to a specific school of law, and reasons ofrevelation, however, he neglected the ascription of scholars' views to theirauthorities, and he was not interested in giving preference to a one view overanother.